IoT-Based Smart Class System - Fanny Ramadhani; Andy Satria (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2025)
The rapid development of Internet of Things (IoT) technology has significantly transformed various sectors, including education. This study proposes an IoT-Based Smart Class System designed to enhance the effectiveness, efficiency, and interactivity of the learning environment. The proposed system integrates IoT devices such as sensors, microcontrollers, and networked actuators to monitor and control classroom conditions, including lighting, temperature, occupancy, and learning equipment usage in real time. Data collected from these devices are transmitted to a centralized platform for processing, visualization, and decision support. The system enables automated classroom management, improves energy efficiency, and supports data-driven decision-making for educators and administrators. Experimental results and system evaluation indicate that the implementation of the IoT-based smart classroom improves learning comfort, optimizes resource utilization, and provides a scalable solution for modern educational environments. The findings demonstrate that IoT technology has strong potential to support smart education initiatives and the development of intelligent learning spaces.